Photo-Controlled Adhesives Based on Photoinduced Solid-to-Liquid Transition of an Azobenzene Compound - Niu, Bing; Chen, Mingsen; Zhao, Xiaolei; Liu, Yuanli; Wu, Si (Organic Materials, 2020)
The development of photo-controlled adhesives can overcome the problems associated with daily lives and industrial applications. Adhesion is a multidiscipline field of engineering, physics, and chemistry. The solid-to-liquid transformation of light-controlled adhesives can be used for direct bonding onto diverse surfaces. Here, a photoresponsive azobenzene compound is developed for photo-controlled adhesion. The azobenzene compound 4, 4'-hexyl diacrylate-3-methylazobenzene (M1) exhibits photoinduced solid-to-liquid transition due to trans–cis photoisomerization. The prepolymer coating based on the azobenzene compound M1 is prepared on an adhesive surface. After UV irradiation, the solid coating was quickly transformed into liquid for adhesion. This photo-controlled adhesive has strong adhesion to different surfaces.
Keywords: azobenzenes; photoinduced solid-to-liquid transition; prepolymer coating; photo-controlled adhesives